Romania, the European Union and Russia - Ion Muschei (CES Working Papers, 2016)
Throughout history, international relationships have always witnessed the forming of alliances, bilateral agreements, mutual treaties, conventions, partnerships or founding organizations. All these agreements have lasted as long as all the actors involved have shared a common interest, but during conflictual periods they have been reduced to simple sheets of paper. Certainly, the very same states have, again and again, been both `friends' and `enemies' because in international relations “nations have no permanent friends or allies, they only have permanent interests.”1 Thus, in a world of growing interdependence and continuous change, globalization will not turn this world into a flat one, nor will it bring history to an end. On the contrary, it will generate new threats and will make differences more obvious and more striking. Moreover, the events that have taken place during the last few years clearly point this out. Starting with the 2013 Summit in Vilnius, the European Neighbourhood Policy and the Eastern Partnership, in particular, have brought about major direct changes in Eastern Europe and indirect ones in Bruxelles, culminating in territorial changes in the immediate proximity of Romania. Taking into account both its significant geopolitical and geostrategic location and its membership to the European Union, Romania finds itself, as always, at a crossroads. In this context, the present paper aims at determining the role the European Union plays in Romania's relationship with Russia.
Keywords: F51; R58; F68; 330; European Union; Eastern Partnership; European Neighbourhood Policy; globalization